(untitled) (Revista Contexto & Saúde, 2023)
The aim of this work is to describe the development of a photo serial album to assist health professionals in the guidelines on the ways of presenting complementary food. This is a study on the production of a serial album with photographs as a visual resource for menus prepared for children. One of the criteria for the creation process was to develop a product that is easy to use and understand by health professionals, about the composition of meals according to the age group of children, from 6 to 12 months. For the production of the serial album, a search was made in the scientific literature, preparation of the menus, preparation of meals, photographic capture of the portioning of the dishes, development of the product layout and graphic printing. The study resulted in a serial album with 12 photographs of menus for main meals and snacks with explanatory text about the different textures and amounts according to the age of the child. Positive eating practices supported by easy-to-use and visually attractive teaching materials such as the serial album produced, favor the promotion of healthy eating in childhood and the formation of an adequate eating behavior, strengthening the construction of good habits for the future.